Characterization of thermoelectric generator (TEG) transducer array for automobile engine application - Go, Raynard A. (Animo Repository, 2009)
The use of thermoelectric generators (TEG) to harness waste heat energy from an automobile’s exhaust is not entirely new. BMW developed a vehicle having installed TEG in its exhaust pipe. The said TEG system generated 200 watts of power by utilizing and connecting several arrays of high powered TEG modules. In another research, about 800 watts of power was generated. Although such products already exist, no study is available as to how these TEGs should be arranged and configured in order to produce optimum power. This study aims at finding the best location for installation of the TEGs along the car’s exhaust system. The characterization of the thermoelectric generator transducer included profiling of heat generated by the car’s engine system and making several arrangements of TEG arrays to generate the required power at a specified voltage.